Access to Justice as a Condition for Serious Judicial Reform - La Rosa Calle, Javier (2009)
This paper aims to explore the right of access to justice in Peru and will focus on developing a new notion of the right of access to justice, taking into account the institutional, social and economic barriers that are presented against. The first part explains the positions on the right of access to justice in the past and raises a new notion to address the issue effectively. The second part develops the institutional barriers such as legal education, the procedural burden, the organization of the Judicial Power and other institutions of justice and their respective budgets. Then, social barriers such as linguistic, cultural and gender are developed. Subsequently, the economic barriers of access to justice are pointed out. Finally, propose measures that could help build an inclusive justice system in order to create a right of access to justice that is effective and real for society.